2017 IEEE International Geoscience and Remote Sensing Symposium (IGARSS) 2017
DOI: 10.1109/igarss.2017.8128260
|View full text |Cite
|
Sign up to set email alerts
|

The Sentinel-1 constellation for InSAR applications: Experiences from the InSARAP project

Abstract: The two-satellite Copernicus Sentinel-1 (S1) constellation became operational in Sep 2016, with the successful in-orbit commissioning of the S1B unit. During, the commissioning phase and early operational phase it has been confirmed that the interferometric performance of the constellation is excellent, with no observed phase anomalies. In this work, we show an analysis of selected performance parameters for the S1 constellation, as well as selected results based on the available data from the first months of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
0
4
0
Order By: Relevance
“…The requirement of an accuracy of 1 mm/y at more that 100 km (<10 nstrain) pushes the technique to its limits [5]. Notwithstanding, it has been demonstrated that, since actual SAR missions are characterized by very stable oscillators [31] and very good orbit knowledge [32,33], such numbers can be considered achievable. The major limitation is atmospheric effects.…”
Section: North Anatolian Fault Datasetmentioning
confidence: 99%
“…The requirement of an accuracy of 1 mm/y at more that 100 km (<10 nstrain) pushes the technique to its limits [5]. Notwithstanding, it has been demonstrated that, since actual SAR missions are characterized by very stable oscillators [31] and very good orbit knowledge [32,33], such numbers can be considered achievable. The major limitation is atmospheric effects.…”
Section: North Anatolian Fault Datasetmentioning
confidence: 99%
“…For example, a strong bias was observed due to an oscillator drift on the Envisat ASAR data (Marinkovic & Larsen, 2013). However, the S1 oscillator appears very stable (Larsen et al., 2017). A multi‐annual TEC change or TEC gradient change could also produce a bias, which could be avoided with GIM‐derived TEC corrections when validated (see subsection 6.3).…”
Section: Discussionmentioning
confidence: 99%
“…a typical swath of future spaceborne SAR's. Fortunately, with Sentinel-1, the drifts are smaller than 10 −9 /year [2] and they can be ignored. One must say that if the oscillator drift can be well modeled, the magnitude of the drift is not decisive but its knowledge is then the crucial point.…”
Section: Instrument and Geometrymentioning
confidence: 99%